Relation of Team Size and Success With Injuries and Illnesses During Eight International Outdoor Athletics Championships - Edouard, Pascal; Richardson, Andy; Navarro, Laurent; Gremeaux, Vincent; Branco, Pedro; Junge, Astrid (Frontiers in Sports and Active Living, 2019)
Introduction: The number of injuries and illnesses during major athletics championships vary according to sex and discipline. They may also differ between countries (national teams) given the differences in training, medical care, nutrition, lifestyle habits, and in travel to the championships. In addition, injuries and illnesses may influence the performance during the championships. Therefore, the aim was to analyse the differences in the injury and illness occurrence during international outdoor athletics championships with regards to the athlete’s country, as well as establishing the potential relationships with the success of the country during the respective championships. Method: The national medical teams and the local organizing committee physicians reported all injuries and illnesses daily on a standardised injury and illness report form during 4 World and 4 European outdoor championships from 2007 to 2018. Results were presented as number of registered athletes, injuries, illnesses and medals (absolute and per 1000 registered athletes), and for countries of different team size. Results: During these 8 championships, a total of 219 different countries participated with a total of 13059 registered athletes who incurred 1315 injuries and 550 illnesses. The number of injuries and illnesses per championships varied between countries. Countries with higher numbers of registered athletes had a higher number of injuries and illnesses, as well as a higher number of medals and gold medals. There were significant positive correlations between number of injuries/illnesses and number of registered athletes, medals, gold medals. Injury and illness numbers per 1000 registered athletes differed between countries and team sizes. Analysing country participation grouped according to the number of registered athletes, there were significant negative correlations between injury/illness and medals/gold medals per 1000 registered athletes. Conclusions: Given the correlation between health problems and country size, we suggest that medical services provision and staff should be adapted to the team size. In groups of different country team sizes, lower number of injuries and illnesses per registered athletes were correlated with higher number of medals and gold medals per registered athletes, which can support that injury and illness prevention should be recognized as a win-win performance-prevention strategy.